Faktor-Faktor yang Mempengaruhi Keputusan Pembelian Kosmetik Halal di Indonesia - Waspada Meliala; Firdha Hidayatullah; Virgilio Cancera Meliala (JURNAL RISET MANAJEMEN (JURMA), 2024)
The halal cosmetics industry in Indonesia is rapidly growing as Muslim consumers become increasingly aware of the importance of products that comply with Islamic principles. This study aims to identify the factors influencing the purchase decisions of halal cosmetic products, including price, brand image, halal certification, religiosity, and brand trust. The research employs a quantitative survey method with a Structural Equation Modeling (SEM) approach to analyze the relationships between variables. The findings indicate that brand trust and awareness of halal certification play a significant role in purchasing decisions. Additionally, religiosity influences consumer awareness of product halalness. This study provides recommendations for producers to emphasize halal aspects, transparency in information, and educational marketing to enhance consumer trust and loyalty.